2011
DOI: 10.1111/j.1478-3231.2011.02560.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary cystadenomas and cystadenocarcinomas: a report of 33 cases

Abstract: Clinical symptoms are unreliable for these diagnoses and their differential diagnosis. Imaging evaluations and CA19-9 are of value for the recognition of cystadenoma and cystadenocarcinoma, but not for their differential diagnosis. Any recurrence of liver cyst after surgery or other treatments should lead one to suspect one of these diseases. Invasive examination and percutaneous fine-needle aspiration cytology are not recommended. Complete excision or careful enucleation should be the first treatment choice f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 21 publications
2
92
0
1
Order By: Relevance
“…(18, 19, 21) The latter theory is supported by the multiple reports of benign epithelium within BCAC specimens. (8, 10, 18, 21, 22) For example, Devaney et al (10) reported malignant transformation in 6 of the 18 BCAC in their series as well as cytological atypia/dysplasia in a number of BCA.…”
Section: Incidence and Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…(18, 19, 21) The latter theory is supported by the multiple reports of benign epithelium within BCAC specimens. (8, 10, 18, 21, 22) For example, Devaney et al (10) reported malignant transformation in 6 of the 18 BCAC in their series as well as cytological atypia/dysplasia in a number of BCA.…”
Section: Incidence and Epidemiologymentioning
confidence: 99%
“…(8, 16, 39) Septal thickening, papillary infolding, and mural nodules are characteristic of BCTs. (40, 41) BCAC is more likely to contain mural or septal nodules and papillary projections.…”
Section: Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Biliary tract tumours are rare entities, more common in women than in men; they can occur in gallbladders or extrahepatic ducts 3 4. They can be classified according to the morphology or histology types.…”
Section: Discussionmentioning
confidence: 99%